Essential plant nutrients impair post‐germination development of Striga in sorghum - Immaculate M. Mwangangi; Lucie Büchi; Steven Runo; Jonne Rodenburg (Plants, People, Planet)
Societal Impact Statement Infestation by the parasitic weed Striga is a major cause of cereal crop production losses on smallholder farms in Africa. Essential plant nutrients play an important indirect role in parasite seed germination, the first prerequisite for successful parasitism. Here, we demonstrate that increasing the nutrient availability for the host plant can also impede Striga development beyond its germination, independent of the resistance levels of the sorghum host. This insight provides additional support for crop protection recommendations to Striga‐affected farmers. Growing a resistant crop variety combined with adequate levels of fertilisers should be the backbone of defence against this parasitic weed. Summary Striga hermonthica is a widespread parasitic weed in sub‐Saharan Africa and an important biotic constraint to sorghum production. Resistant varieties and fertilisers are crucial components of integrated Striga management. N and P fertilisers reduce the production of host‐plant strigolactones, known as Striga germination stimulants, and thereby reduce infection. Whether essential plant nutrients affect the parasite–host interaction beyond Striga germination is unknown. We conducted mini‐rhizotron assays to investigate the effects of macronutrient and micronutrient availability on post‐germination Striga development. Four sorghum genotypes (Framida, IS10978, N13, IS9830) covering the complete array of known mechanisms of post‐attachment resistance were compared with susceptible genotype Ochuti. Plants were infected with pre‐germinated Striga seeds and subjected to four nutrient treatment levels: (1) 25% of the optimal concentration of Long Ashton solution for cereals; (2) 25% macronutrient and optimal micronutrient concentration; (3) optimal macronutrient and 25% micronutrient concentration; and (4) optimal macronutrient and micronutrient concentrations. Compared with the 25% base nutrient level, treatments supplemented with macronutrients reduced the number of viable vascular connections established by pre‐germinated Striga seedlings as well as the total parasite biomass on the sorghum root system. Macronutrient treatment effects were observed across sorghum genotypes, independent of the presence and type of post‐attachment resistance, but appeared to specifically improve mechanical resistance, hypersensitive and incompatibility responses before Striga reaches the host‐root xylem. This study demonstrates, for the first time, that nutrient availability drives Striga parasitism beyond the germination stages. Increased availability of nutrients, in particular macronutrients, enhances host‐plant resistance in post‐attachment stages, reinforcing the importance of current fertiliser recommendations.